Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1203/pdr.0b013e31816c8fe3
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Noninvasive Continuous Finger Arterial Blood Pressure Measurements in Very Young Children, Aged 0–4 Years

Abstract: ABSTRACT:Our goal was to study the feasibility of continuous noninvasive finger blood pressure (BP) monitoring in very young children, aged 0 -4 y. To achieve this, we designed a set of smallsized finger cuffs based on the assessment of finger circumference. Finger arterial BP measured by a volume clamp device (Finapres technology) was compared with simultaneously measured intra-arterial BP in 15 very young children (median age, 5 mo; range, 0 -48), admitted to the intensive care unit for vital monitoring. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…In the same time generally, using non-invasive method is simpler, save, less complications as bleeding and distal limb ischemia and less cost than invasive method. (32) These results were in line with Andriessen et al (33) who concluded that in pediatric patients, non-invasive ABP reading showed worthy similarities with invasive ones. Additionally, Gevers et al (34) concluded presence of a big similarity between invasive and non-invasive ABP reading.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In the same time generally, using non-invasive method is simpler, save, less complications as bleeding and distal limb ischemia and less cost than invasive method. (32) These results were in line with Andriessen et al (33) who concluded that in pediatric patients, non-invasive ABP reading showed worthy similarities with invasive ones. Additionally, Gevers et al (34) concluded presence of a big similarity between invasive and non-invasive ABP reading.…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, it is important to consider using appropriate cuff pressure for age to measure noninvasive arterial blood pressure. Moreover, Andriessen (33) established in children that applying cuff pressure correctly seemed to be very serious when measuring ABP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bias for MAP and DAP was lower (Ϫ18.6% and Ϫ18.8%, respectively) and in concordance with results in adults. 17,18 Interestingly, Andriessen et al 6 using similar prototype equipment, observed a smaller bias in newborns. They observed that the (not reconstructed) mean finger pressure was on average about 5 mm Hg lower than the invasive mean pressure.…”
Section: Discussionmentioning
confidence: 95%
“…4,5 Recently, prototype small finger cuffs especially designed for the pediatric population were developed by BMEYE, and a pilot study has shown promising results. 6 In the current study, we used these prototype pediatric finger cuffs (four different sizes) and pediatric software to compare this new noninvasive continuous blood pressure measurement with intraarterially measured blood pressure in critically ill children. In a subgroup, we also compared IAP measurements with the standard NIBP technique.…”
mentioning
confidence: 99%